ANALISIS KESALAHAN BAHASA INGGRIS DALAM KARYA TULIS SISWA DI SMA N 1 KAWANGKOAN - Piri, Sendis Elisabeth; Kodong, Fentje; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis research entitled â€œError Analysis in Studentsâ€™ English Writing at SMA N 1 Kawangkoanâ€ is an attempt to to identify, classify, and analyzeÂ  the kinds of errors in the use of simple past tense made from students of SMA N 1 Kawangkoan. The signifiacance of this research are theoretically to to apply the theory of error analysis in English narrative writing and practically this research is expected to help students and readers to understand the error analysis in English narrative writings. In the preparation, writer reads some books and journals about error analysis and do a preliminary research. Data were collected by the studentsâ€™ assignments about narrative writings. The method used in this research is descriptive. Ellisâ€™ theory is used to analyze the dataÂ  of the narrative writing made by students of SMA N 1 Kawangkoan. The sample is taken from Students in 2 Binsus Classes which are Grade X Science Binsus and Grade X Social. The result of this research shows that there are three kinds of error made by students. First,Â  Omission which 36% of students made error and get 9 types of omission . Second, MisinfromationÂ  which 55% students made error and get 9 types of misinformation and the last Misordering which 9% students made error and get 3 types of misordering . These research shows that students are still confused in using the simple past tense in their writings. These research is expected to give contribution toÂ  the education institutions in errors made by students so that the institutions can find a solution to overcome the errors in their English using.Â Keywords : Simple past tense, error analysis, writing